Testicular tumor arising from an intra-abdominal undescended testis in a 1-year-old child: a case report and literature review - Qiongzhang Xia; Tongshuai Kuang; Xiaokun Lin; Xiaokun Lin; Hua Zhang (Frontiers Media S.A., 2023)
ObjectivesTesticular tumors in the intra-abdominal undescended testis are rare in children, and their management remains challenging. The aim was to present a case report and review of the literature about diagnosis and treatment of testicular tumors arising from undescended intra-abdominal testis in children.MethodsIn this study, we retrospectively analyzed the clinical records of a 1-year-old male patient admitted to pediatric surgery in March 2022 with a testicular tumor originating in the intra-abdominal undescended testis. Furthermore, medical literature published in English during the last three decades was systematically searched through the databases of Medline, PubMed, and Google Scholar.ResultsThe patient underwent laparoscopic orchiopexy and tumor excision. The operation was uneventful, and the patient recovered well without complications. An 8-month follow-up showed no recurrence of the teratoma after postoperative pathology. The literature search resulted in the retrieval of 16 non-duplicate articles, and 16 patients were included in this review. The cases included six cases of left cryptorchidism and 10 cases of right cryptorchidism, with an average age of 15.3 months. The largest transverse diameter of the tumors ranged from 1.8 to 12.5 cm, with an average tumor length of 6.7 cm. All patients underwent surgical treatment, including three cases of laparoscopic orchiectomy, a sole case of a conversion of inguinal incision to laparotomy and orchiectomy, and 12 cases of laparotomy and orchiectomy. Postoperative pathology revealed 12 cases of mature teratoma, two cases of immature teratoma, one case of yolk sac tumor, and a single case of embryonic carcinoma combined with yolk sac tumor. 11 patients were followed up, and one of them recurred.ConclusionAbdominal ultrasound (US) or abdominal computer tomography (CT) should be performed in cases of undescended testis suspected to have testicular tumors on clinical findings. The most common type of intra-abdominal testicular tumor is mature teratomas. Early diagnosis and prompt surgical intervention resulted in an excellent outcome.